( 1 + x ) 2 + ( 1 + x ) 3 + ( 1 + x ) 4 + ⋯ + ( 1 + x ) 4 9 + ( 1 + m x ) 5 0
Let m be the minimum positive integer such that the coefficient of x 2 in the expansion above is ( 3 n + 1 ) ( 3 5 1 ) , where n is an integer.
Find n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Similar to what i did!
Log in to reply
Nice question to use the hockey-stick identity on, as we know that
k = 2 ∑ 5 0 ( 2 k ) = ( 3 5 1 ) ,
so we can quickly see that if m = 1 then we can set n = 0 .
Noting that the equation m 2 = 5 1 n + 1 can be written as
m 2 − 1 = 5 1 n ⟹ ( m − 1 ) ( m + 1 ) = 3 ∗ 1 7 ∗ n ,
to find other ( m , n ) pairings we need to choose n so that 3 ∗ 1 7 ∗ n can be factored into a product of two integers that differ by 2 . The next solution is then ( 1 6 , 5 ) followed by
( 3 5 , 2 4 ) , ( 5 0 , 4 9 ) , ( 5 2 , 5 3 ) , ( 6 7 , 8 8 ) , ( 8 6 , 1 4 5 ) , ( 1 0 1 , 2 0 0 ) , ( 1 0 3 , 2 0 8 ) , ( 1 1 8 , 2 7 3 ) , . . . . .
Notice, the final coefficient of x 2 in the sum is Σ n = 2 4 9 ( 2 n ) + ( 2 5 0 ) ⋅ m 2 . From observation of the pascal's triangle (And I'm sure there is some property that shows this), we see that if m = 1 , the sum of these is equal to ( 3 5 1 ) 1 1 , 1 1 , 2 , 1 1 , 3 , 3 , 1 1 , 4 , 6 , 4 , 1 1 , 5 , 1 0 , 1 0 , 5 , 1 1 , 6 , 1 5 , 2 0 , 1 5 , 6 , 1 . . . Notice, going down the ( 2 n ) line up to n = 5 , we get 1 + 3 + 6 + 1 0 = 2 0 = ( 3 6 ) . This can be applied up to any other n , so now, we can solve for n such that m = 1 . ( 3 5 1 ) = ( 3 n + 1 ) ⋅ ( 3 5 1 ) 3 n + 1 = 1 3 n = 0 n = 0
(1 + 3 + 6 + 10 + ....+ 49C2)=(1/6)(n)(n+1)(n+2), where n=48.
19600 + (35 m)^2 = (3n+1) 20825. So, m^2 = 17(3n+1) – 16 .The smallest n=0.
Problem Loading...
Note Loading...
Set Loading...
The coefficient of x 2 in the expansion is given by:
k = 2 ∑ 4 9 ( 2 k ) + ( 2 5 0 ) m 2 k = 2 ∑ 4 9 2 k ( k − 1 ) + 2 5 0 ⋅ 4 9 m 2 k = 2 ∑ 4 9 ( k 2 − k ) + 5 0 ⋅ 4 9 m 2 6 4 9 ⋅ 5 0 ( 2 ⋅ 4 9 + 1 ) − 1 − 2 4 9 ⋅ 5 0 + 1 + 5 0 ⋅ 4 9 m 2 6 9 9 − 2 1 + m 2 1 6 + m 2 m 2 = ( 3 n + 1 ) ( 3 5 1 ) = ( 3 n + 1 ) 3 ⋅ 2 5 1 ⋅ 5 0 ⋅ 4 9 = 1 7 ⋅ 5 0 ⋅ 4 9 ( 3 n + 1 ) = 1 7 ⋅ 5 0 ⋅ 4 9 ( 3 n + 1 ) = 1 7 ( 3 n + 1 ) = 5 1 n + 1 7 = 5 1 n + 1
⟹ min ( m ) = 1 , when n = 0 .